Android application for independent real time locating system and its academic application - Sharma, Ritika. (2014)
Indoor positioning has been researched and developed significantly in the past few years because the applications used for tracking person or object in the indoor environment are increasing in importance and purposes. It has also gained significant attention over the recent years with low-cost and low-power wireless standards like Zigbee.